The Cracking of 1-Octadecanol Into Short Chain Alkane and Alkene Compounds - Handoko, Donatus Setyawan Purwo; Triyono (PT FORMOSA CENDEKIA GLOBAL, 2025)
Research has been carried out on the cracking mechanism of 1-octadecanol into short chain alkane and alkene compounds using a cracking technique using a Fluid Fixed Bed reactor, which is operated at temperatures between 450 oC to 500 oC for 30 minutes. The catalyst is positioned so that the feed vapor passes through a number of catalysts. The resulting product was analyzed using GC-MS. The results obtained are as follows. With the Ni/ZSiA catalyst, the catalytic hydrogenation of 1-octadecanol to 1-octadecene reached 20.21 percent, 5-octadecene reached 14.37 percent, and 9-octadecene reached 10.40 percent. The main product of catalytic hydrogenation is 1-octadecene. The results obtained at a hydrogen flow rate of 10 mL/minute and a temperature of 450 oC produce maximum alkane and alkene products < C12 (15.29%)